What is the self-reported person-centred care competency and observed implementation of final year audiology students during their clinical encounters? - Mustapha, Gaafitha (Division of Communication Sciences and Disorders, 2025)
Background: Person-centred care (PCC) is described as a set of principles and behaviours which are practiced together to ensure that clients' management goals and health needs are met. Practicing PCC in healthcare may have positive outcomes on all parties involved, including the professional, client, and organization. In audiology, the majority of PCC research conducted thus far has been focused on practicing audiologists and in higher income countries. Many of the studies have also focused on PCC preferences, with fewer studies exploring the implementation of PCC in clinical practice. Studies exploring PCC competency and implementation in South Africa are lacking. Furthermore, a paucity of research exists in South African clients' perspectives on PCC. Study aims: 1) explore the self-reported PCC competency of final year audiology students. 2) describe students' observable PCC implementation during clinical encounters and how audiology clients perceived implementation thereof. Methodology: This study utilized an exploratory sequential mixed methods design. Quantitative and qualitative data were collected across two phases. In phase one, an adapted PCC Competency questionnaire (17 items) was administered to final year audiology students via an online platform (Google forms). In phase two, PCC implementation observations were administered in student-led clinical encounters with clients at Groote Schuur Hospital. Clients were invited to participate in a semi-structured interview after the clinical appointment to document their perceptions of PCC implementation in the student-led session. Data collection tools used in the study were the Person-Centred Care Competency Scale (adapted from Hwang, 2015), PCC Observational Checklist (Tai, Barr, & Woodward-Kron, 2019), and the Patient/Carer Questionnaire (Ida Institute, n.d.). Data analysis was conducted using descriptive analysis and content analysis in phase one and two respectively. Results: In phase one 11 student participants (47.8% of the total class) completed the questionnaire. All of the participants were female identifying, and aged between 21 and 25 years old. Findings from the PCC Competency scale showed students perceived themselves to be competent in PCC. Students demonstrated competency in eliciting client and family perspectives. However, students demonstrated lesser competency in providing access to resources and assisting the client with decision-making. Six participants were invited to participate in phase two of the study. Of the six students invited to enrol into phase two of the study, one participant volunteered to participate (n = 8.3%) and was observed during a clinical encounter with an audiology client. The student displayed a majority of the PCC communication functions listed in the Observational Checklists. No client participants were enrolled in the study due to transport limitations after the clinical encounter. Additional client participants were not recruited due to lack of student participation in phase two of the study. Conclusion: The study's findings suggest that final year audiology students perceived themselves to be competent in PCC. From the observation it was evident that PCC was implemented during the clinical encounter. A larger sample size should be included in future studies to allow for generalizability of the findings. Future research should explore PCC competency and implementation in conjunction with additional participant demographics e.g. sex, age and home province. Client perspectives of PCC implementation should also be explored qualitatively. Declaration and funding This study was funded under a department of Health and Rehabilitation Sciences Postgraduate funding scholarship that is linked to the Principal Investigator, V. Hlayisi's Building Research Active Academic Scholars fund. The opinions expressed and conclusions contained in this thesis, are those of the author and are not necessarily attributed to the funder.